H-1 NMR determination of adulteration of anabolic steroids in seized drugs - Moura Ribeiro, Marcos VinIcius de [UNESP]; Boralle, Nivaldo [UNESP]; Felippe, Lidiane Gaspareto [UNESP]; Pezza, Helena Redigolo [UNESP]; Pezza, Leonardo [UNESP] (Elsevier B.V., 2018)
Counterfeiting and adulteration of pharmaceuticals is a prevalent problem worldwide and represents a major health risk to the population, with anabolic steroids being one of the main classes of drugs consumed and obtained from dubious sources. In this work, we propose the use of the H-1 NMR technique to evaluate formulations containing anabolic steroids, with analysis of 40 samples of anabolic drugs that are used in injectable and capsule forms. The samples analyzed presented the following active ingredients: testosterone propionate, testosterone phenylpropionate, testosterone isocaproate, testosterone decanoate, testosterone cypionate, testosterone undecanoate, stanozolol, drostanolone propionate, trenbolone acetate, oxymetholone, and methandrostenolone. The H-1 NMR spectroscopic measurements were performed using a 600 MHz Bruker Avance III spectrometer, with deuterated chloroform (CDCl3) containing 0.1% TMS as solvent. Of the 40 samples analyzed, eight did not show the presence of the active principle stated on the label. Three types of adulteration were found in the analyzed samples: absence of the active ingredient, adulteration with other substances, and concentration values below those indicated on the label. Sildenafil citrate was found in four samples. The GC-MS technique was used to confirm the adulteration results found using H-1 NMR. Quantitative determination by NMR was performed using internal standard and ERETIC 2 methods, and the results obtained were statistically the same.
Keywords: Anabolic steroids; H-1 NMR; Authenticity; Adulteration; Quantification